1987
DOI: 10.1902/jop.1987.58.12.837
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Invasion in Experimental Gingivitis in Man

Abstract: Gingival biopsies of the mesial papilla area of the first molar were obtained from each patient at 0‐, 14‐ and 21‐day intervals during plaque formation. The biopsies were fixed, serially sectioned, and Gram‐stained. The incidence and distribution of the bacteria‐like structures were studied by microscopy. In all the specimens the bacterial nature of Gramstained material was substantiated. In the epithelium the highest number of bacteria was found at the outer layer of marginal oral epithelium, sulcular epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…The combination of both staining patterns (discrete and diffuse) resembled that reported previously in epithelial and connective tissues of gingival specimens from sites associated with experimental gingivitis, chronic periodontitis, and localized aggressive periodontitis probed with antiserum raised against whole P. gingivalis, Actinobacillus actinomycetemcomitans, and Capnocytophaga sputigena cells and stained with peroxidase-DAB (64)(65)(66)(67)(68). The discrete immunostaining observed in the localized aggressive periodontitis and chronic periodontitis specimens probed with antisera raised against these species was subsequently shown to represent bacterial cells (64,65,68).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The combination of both staining patterns (discrete and diffuse) resembled that reported previously in epithelial and connective tissues of gingival specimens from sites associated with experimental gingivitis, chronic periodontitis, and localized aggressive periodontitis probed with antiserum raised against whole P. gingivalis, Actinobacillus actinomycetemcomitans, and Capnocytophaga sputigena cells and stained with peroxidase-DAB (64)(65)(66)(67)(68). The discrete immunostaining observed in the localized aggressive periodontitis and chronic periodontitis specimens probed with antisera raised against these species was subsequently shown to represent bacterial cells (64,65,68).…”
Section: Discussionsupporting
confidence: 73%
“…A similar pattern of diffuse immunostaining was also observed interspersed among discrete spots in gingivitis and periodontitis tissue probed with antiserum to P. gingivalis and to other species using an immunoperoxidase technique (65)(66)(67)(68). It is likely that the diffuse immunostaining in our diseased specimens represented RgpAKgp at lower concentrations in the tissues (92).…”
Section: Discussionsupporting
confidence: 73%
“…The data from the present study demonstrated that the bacteria present in specimens from the dento-gingival tissues of the beagle dog were predominantly cocci, but not filamentous or rod-shaped bacteria. This finding is in contrast to the reports by Saghe et al [7][8][9][10][11]14 and Ericsson et al.20 who observed rods, filaments, and cocci in cases of advanced Periodontitis. The discrepancy between the present study and these reports could be due to some fault of the modified gram stain used in the present study.…”
Section: Discussioncontrasting
confidence: 80%
“…Gingivitis involves bacterial infection with a range of Gram-positive and Gram-negative bacteria that invade the superficial gingival tissues [32]. During progression of the gingival disease, the epithelium becomes ulcerated to expose the underlying connective tissues and blood capillaries and facilitates entry of biofilm organisms or their products (e.g.…”
Section: Discussionmentioning
confidence: 99%